Summaries of Micro motion Mechanisms - 罗建勤; 曾韬 (Jixie chuandong)
At present, micro motion mechanisms are usually actuated by elastic deformation, linear motor, mechanical transmission, electrical magnet and intelligent materials. The structures, principle, characters and some applications several types of micro motion mechanisms are introduced and compared with eath other in this paper.